A history of development in brain chips in present and future - Talha, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Most high-speed calculations are based on big data sets. However, constrained by Moore’s Law, the number of devices cannot increase without a limit. A suitable estimate with high accuracy and capacity is needed. Brain-like computation mimics the function of information analysis in human brains. Brain-like chips are hardware applying brain-like structure and analysis. Based on the neutron structure, brain-like chips can overcome the limitation of Von Neumann and improve both speed and complexity of calculation. The power consumption will decrease at the same time. In this essay, we will talk about the performances of several typical latest chips and discuss the difficulties and future development of brain-like chips.